2015
DOI: 10.4081/monaldi.2011.243
|View full text |Cite
|
Sign up to set email alerts
|

Lung Transplantation and Endoscopic Issues

Abstract: In the last 20 years lung transplantation has become a therapeutic reality for many end-stage parenchymal and vascular lung diseases; despite the difficulty in finding donors, the results are currently satisfactory [1][2][3].Infections, lung rejection and airway complications are the major causes of morbidity and mortality in patients who undergo lung or heartlung transplantation (LT) [4,5]. The usefulness of transbronchial lung biopsy (TLB) was reported for the first time in 1988 [6]. Since then TLB has becom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“… 97 , 98 Fiberoptic bronchoscopy of donors may maximize organ utilization through airway clearance, anatomical assessment, and identification of infectious organisms. 99 , 100 , 101 The ISHLT BAL survey showed that most (72.4%) perform bronchoscopy for culture analysis. Bronchoscopy and sample collection in donor assessment is uniformly done before procurement and varies from several days before to intraoperatively during the procurement 98 , 102 (Association of Organ Procurement Organizations policy and Organ Procurement and Transplantation Network/United Network of Organ Sharing policy).…”
Section: Statementsmentioning
confidence: 99%
See 3 more Smart Citations
“… 97 , 98 Fiberoptic bronchoscopy of donors may maximize organ utilization through airway clearance, anatomical assessment, and identification of infectious organisms. 99 , 100 , 101 The ISHLT BAL survey showed that most (72.4%) perform bronchoscopy for culture analysis. Bronchoscopy and sample collection in donor assessment is uniformly done before procurement and varies from several days before to intraoperatively during the procurement 98 , 102 (Association of Organ Procurement Organizations policy and Organ Procurement and Transplantation Network/United Network of Organ Sharing policy).…”
Section: Statementsmentioning
confidence: 99%
“…Reports on airway sampling for microbiological assessment of potential organ donors have included tracheal aspirates, BW, and BAL. 97 , 99 , 100 , 103 , 104 , 105 , 106 Precise explanation of the sampling methodology is rarely available, making evidence-based practice recommendations problematic. The ISHLT BAL survey demonstrated significant variation in donor airway sampling methodology and technique; however, bronchoscopic aspiration of secretions (35.2%) and large airway BW (28.6%) were by far the most common practices.…”
Section: Statementsmentioning
confidence: 99%
See 2 more Smart Citations